2021
DOI: 10.3390/antibiotics10091031
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Impact on Clinical Outcomes of Bloodstream Infections in Patients Hospitalised with COVID-19: A Prospective Cohort Study

Abstract: With the aim of describing the burden and epidemiology of community-acquired/healthcare-associated and hospital-acquired bloodstream infections (CA/HCA-BSIs and HA-BSIs) in patients hospitalised with COVID-19, and evaluating the risk factors for BSIs and their relative impact on mortality, an observational cohort study was performed on patients hospitalised with COVID-19 at San Paolo Hospital in Milan, Italy from 24 February to 30 November 2020. Among 1351 consecutive patients hospitalised with COVID-19, 18 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Cona et al [ 28 ] studied incidence, risk factors and outcome of patients with BSI and COVID-19, showing that the most common cause of BSI in a cohort of COVID-19 patients was Staphylococcus aureus and that CA-BSI were as frequent as HA-BSI32.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the presence of BSI increased the length of the hospital stay [ 28 ]. Similarly, our data showed that any kind of bacterial superinfection, with particular reference to HAIs, significantly increased the length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe forms are complicated by hypoxemic acute respiratory failure requiring intensive care unit (ICU) admission [ 3 , 4 ]. In these patients, secondary infections, both bacterial and fungal, have been increasingly reported [ 5 , 6 , 7 , 8 , 9 ], resulting in the widespread use of antibiotics for the empirical treatment of suspected as well as of microbiologically confirmed infections, hence contributing to an increase in multidrug-resistant bacteria and fungi and increased costs of care [ 10 ].…”
Section: Introductionmentioning
confidence: 99%